Analysis of the Influence of Brand Image and Digital Marketing on the Purchase Decision of Sharia Mutual Fund Bibit in Java, Indonesia - Dila Meita Maulidasari; Irmayanti Hasan (Program Studi Ekonomi Syariah, Fakultas Agama Islam Universitas Islam Riau, 2024)
Bibit is an application that offers one of the investment instruments, namely mutual funds. The size of the sharia market in Indonesia is utilized by Bibit by providing sharia mutual funds. Sharia mutual funds and conventional mutual funds have differences in management principles, securities investment portfolios, and types of contracts. This study aims to analyze the influence of brand image and digital marketing on the purchase decision of Bibit Sharia Mutual Fund in Java, Indonesia. This type of research is quantitative research with an explanatory research method. The location of this research is in Indonesia, especially on the island of Java. The sample used was 180 respondents. The data collection technique uses primary data such as questionnaires and secondary data. The data analysis technique uses Statistical Product and Service Solutions (SPSS) software version 25. The results of this study show that digital marketing variables have a positive and significant effect on the purchase decision of Bibit sharia mutual funds, brand image and digital marketing variables have a combined effect on the purchase decision of Bibit sharia mutual funds. Meanwhile, the brand image variable has a positive but not significant effect on the decision to purchase Bibit sharia mutual funds. This happens because the products offered cannot satisfy users, do not have clear characteristics and are considered less useful by users, especially for users who live on the island of Java.